2017
DOI: 10.1590/s0100-736x2017000400011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of the organic extract of Cladonia substellata Vainio and usnic acid against Staphylococcus spp. obtained from cats and dogs

Abstract: It contains several secondary metabolites with biological activity, including usnic acid, which has exhibited a wide range of biological activities. The aim of this study was to evaluate the in vitro antimicrobial activity of the organic extract of C. substellata and purified usnic acid. Initially, Staphylococcus spp., derived from samples of skin and ears of dogs and cats with suspected pyoderma and otitis, were isolated and analyzed. In antimicrobial susceptibility testing against Staphylococcus spp., 77% (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
5
0
2
Order By: Relevance
“…It is present in different species of lichens as a product of the secondary metabolism. A series of in vitro studies demonstrated not only anti-inflammatory, antioxidant, antitumor, and antiviral properties, but also a potent antibacterial activity against mycobacteria and several Gram-positive and Gram-negative bacteria [15][16][17][18]. Along with these data, the interest in this substance has risen since it could be used as a potential antimicrobial compound.…”
Section: Introductionmentioning
confidence: 99%
“…It is present in different species of lichens as a product of the secondary metabolism. A series of in vitro studies demonstrated not only anti-inflammatory, antioxidant, antitumor, and antiviral properties, but also a potent antibacterial activity against mycobacteria and several Gram-positive and Gram-negative bacteria [15][16][17][18]. Along with these data, the interest in this substance has risen since it could be used as a potential antimicrobial compound.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos sobre a atividade antimicrobiana de substâncias liquênicas normalmente relatam a maior sensibilidade de bactérias Gram-positivas a extratos de diferentes espécies de fungos liquenizados 13,14,15,16,17 . Concomitante a isso, alguns autores reportaram a ineficácia dessas substâncias contra cepas de bactérias Gram-negativas 18,19 .…”
Section: Discussionunclassified
“…Usnic acid was found to be a good antimicrobial agent when compared to streptomycin [90]. The (+)-usnic acid produced by Cladonia arbuscula (have antimycobacterial activity) [91], and the (-) usnic acid produced by Cladonia leptoclada (have anti-tumour activity) [92]. Odimegwu DC, et al [93] and Bhattacharjya R, et al [94], also reported that, usnic acid produced by Pseudocyphellaria glabra and Pseudocyphellaria homoeophylla have antiviral, antimicrobial and cytotoxic activities.…”
Section: Usnic Acidmentioning
confidence: 96%